DEFICIENCIES IN ENACTING ARTICLE 44 OF ROMANIAN LAW NO.111/1996 REGARDING THE SAFE DEPLOYMENT, REGULATION, AUTHORIZATION AND CONTROL OF NUCLEAR ACTIVITIES - Sorin-Alexandru VERNEA (Challenges of the Knowledge Society)
In this paper, the author analyses the main practical issues that can be discussed when enacting the provisions of article 44 of Romanian Law no.111/1996 regarding the safe deployment regulation, authorization and control of nuclear activities. The paper is structured in two parts. The first aims at pointing out the particularities of the incrimination discussed, by reference to its constitutive content, and the second part adapts the mechanism of the Romanian Constitutional Court Decision no.405/2016 to the provision analyzed, in order to comply with the regulation of art.73, paragraph 3, letter h of the Romanian Constitution. The author concludes that the only effective way to prevent the deficiencies previously discussed is the intervention of the legislator, reason for which a de lege ferenda proposal has been made.